2017
DOI: 10.3386/w23890
|View full text |Cite
|
Sign up to set email alerts
|

Paralyzed by Panic: Measuring the Effect of School Closures during the 1916 Polio Pandemic on Educational Attainment

Abstract: The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 14 publications
0
24
0
3
Order By: Relevance
“…However, little is known on how to set up and deliver home education effectively under the unique conditions of the pandemic. While for some children the extended period at home is likely to have distinct positive benefits, research prior to COVID‐19 on substantial externally driven disruptions in schooling has shown adverse effects on child achievement and well‐being (Meyers & Thomasson, 2017; Sunderman & Payne, 2009). The outcomes for the individual child are likely to depend on the capacity of families to step in and effectively support curriculum delivery at home.…”
Section: Research Priority Domainsmentioning
confidence: 99%
“…However, little is known on how to set up and deliver home education effectively under the unique conditions of the pandemic. While for some children the extended period at home is likely to have distinct positive benefits, research prior to COVID‐19 on substantial externally driven disruptions in schooling has shown adverse effects on child achievement and well‐being (Meyers & Thomasson, 2017; Sunderman & Payne, 2009). The outcomes for the individual child are likely to depend on the capacity of families to step in and effectively support curriculum delivery at home.…”
Section: Research Priority Domainsmentioning
confidence: 99%
“…Beyond estimates of immediate impacts, the literature also provides some insights on the long-lasting impacts of shocks and resulting parental concerns around school safety. Meyers and Thomasson (2017) document that when schools reopened after the 1916 polio pandemic, many parents were reluctant to let their children attend. The authors found that young people who were aged 14–17 during the pandemic, later showed lower overall educational attainment compared to slightly older peers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whatever the effect of school closure on the spread of the disease, there is consensus that school closures will entail a learning loss for children and young adults currently enrolled in school. Evidence from the 1916 polio pandemic (Meyers and Thomasson 2017); World War II (Ichino and Winter-Ebmer 2004); and various natural disasters (Andrabi, Daniels and Das 2020; Ceyhan and Ceyhan 2007; Sacerdote 2012; Thamtanajit 2020) shows that interrupting normal schooling has long-lasting impacts. School closures affect learning in two ways, according to Azevedo and others (2020).…”
Section: Education Impactsmentioning
confidence: 99%